Analisis LD DLQ Tipologi Kabupaten Semarang Jawa Tengah - Adinda Nurhalizah; Dia Ayu Rifatus Sholikah; Dwi Meilinda Putri; Fahrizal Taufiqqurrachman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the economic structure and dynamics of Semarang Regency, Central Java Province, using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and sectoral typology approaches. Sectoral analysis is essential to identify leading sectors, potential sectors, and the direction of regional economic transformation to support local-based development planning. The novelty of this study lies in the simultaneous application of LQ and DLQ analyses combined with sectoral typology to capture both comparative advantages and future growth prospects of regional economic sectors. The research employs a quantitative descriptive method using secondary data of Gross Regional Domestic Product (GRDP) of Semarang Regency and Central Java Province at constant prices by industrial origin for the period 2018–2023. The results indicate that the manufacturing sector, agriculture, and wholesale and retail trade are the leading sectors contributing significantly to the regional economy. The DLQ analysis reveals that several leading sectors exhibit sustainable growth potential. This study concludes that strengthening leading sectors and developing potential sectors are key strategies for accelerating economic growth in Semarang Regency.